Vascular Cell Adhesion Molecule 1, Intercellular Adhesion Molecule 1, and Cluster of Differentiation 146 Levels in Patients with Type 2 Diabetes with Complications - Hocaoglu-Emre, F. Sinem; Saribal, Devrim; Yenmis, Guven; Guvenen, Guvenc (Endocrinology and metabolism (Seoul), 2017)
Type 2 diabetes mellitus (T2DM) is a multisystemic, chronic disease accompanied by microvascular complications involving various complicated mechanisms. Intercellular adhesion molecule 1 (ICAM-1), vascular cell adhesion molecule 1 (VCAM-1), and cluster of differentiation-146 (CD146) are mainly expressed by endothelial cells, and facilitate the adhesion and transmigration of immune cells, leading to inflammation. In the present study, we evaluated the levels of soluble adhesion molecules in patients with microvascular complications of T2DM. Serum and whole blood samples were collected from 58 T2DM patients with microvascular complications and 20 age-matched healthy subjects. Levels of soluble ICAM-1 (sICAM-1) and soluble VCAM-1 (sVCAM-1) were assessed using enzyme-linked immunosorbent assay, while flow cytometry was used to determine CD146 levels. Serum sICAM-1 levels were lower in T2DM patients with microvascular complications than in healthy controls (P<0.05). No significant differences were found in sVCAM-1 and CD146 levels between the study and the control group. Although patients were subdivided into groups according to the type of microvascular complications that they experienced, cell adhesion molecule levels were not correlated with the complication type. In the study group, most of the patients were on insulin therapy (76%), and 95% of them were receiving angiotensin-converting enzyme (ACE)-inhibitor agents. Insulin and ACE-inhibitors have been shown to decrease soluble adhesion molecule levels via various mechanisms, so we suggest that the decreased or unchanged levels of soluble forms of cellular adhesion molecules in our study group may have resulted from insulin and ACE-inhibitor therapy, as well as tissue-localized inflammation in patients with T2DM.